Accuracy of four intraoral scanners in oral implantology: a comparative in vitro study - Mario Imburgia; Silvia Logozzo; Uli Hauschild; Giovanni Veronesi; Carlo Mangano; Francesco Guido Mangano (BMC, 2017)
Abstract Background Until now, only a few studies have compared the ability of different intraoral scanners (IOS) to capture high-quality impressions in patients with dental implants. Hence, the aim of this study was to compare the trueness and precision of four IOS in a partially edentulous model (PEM) with three implants and in a fully edentulous model (FEM) with six implants. Methods Two gypsum models were prepared with respectively three and six implant analogues, and polyether-ether-ketone cylinders screwed on. These models were scanned with a reference scanner (ScanRider®), and with four IOS (CS3600®, Trios3®, Omnicam®, TrueDefinition®); five scans were taken for each model, using each IOS. All IOS datasets were loaded into reverse-engineering software, where they were superimposed on the reference model, to evaluate trueness, and superimposed on each other within groups, to determine precision. A detailed statistical analysis was carried out. Results In the PEM, CS3600® had the best trueness (45.8 ± 1.6μm), followed by Trios3® (50.2 ± 2.5μm), Omnicam® (58.8 ± 1.6μm) and TrueDefinition® (61.4 ± 3.0μm). Significant differences were found between CS3600® and Trios3®, CS3600® and Omnicam®, CS3600® and TrueDefinition®, Trios3® and Omnicam®, Trios3® and TrueDefinition®. In the FEM, CS3600® had the best trueness (60.6 ± 11.7μm), followed by Omnicam® (66.4 ± 3.9μm), Trios3® (67.2 ± 6.9μm) and TrueDefinition® (106.4 ± 23.1μm). Significant differences were found between CS3600® and TrueDefinition®, Trios3® and TrueDefinition®, Omnicam® and TrueDefinition®. For all scanners, the trueness values obtained in the PEM were significantly better than those obtained in the FEM. In the PEM, TrueDefinition® had the best precision (19.5 ± 3.1μm), followed by Trios3® (24.5 ± 3.7μm), CS3600® (24.8 ± 4.6μm) and Omnicam® (26.3 ± 1.5μm); no statistically significant differences were found among different IOS. In the FEM, Trios3® had the best precision (31.5 ± 9.8μm), followed by Omnicam® (57.2 ± 9.1μm), CS3600® (65.5 ± 16.7μm) and TrueDefinition® (75.3 ± 43.8μm); no statistically significant differences were found among different IOS. For CS3600®, For CS3600®, Omnicam® and TrueDefinition®, the values obtained in the PEM were significantly better than those obtained in the FEM; no significant differences were found for Trios3®. Conclusions Significant differences in trueness were found among different IOS; for each scanner, the trueness was higher in the PEM than in the FEM. Conversely, the IOS did not significantly differ in precision; for CS3600®, Omnicam® and TrueDefinition®, the precision was higher in the PEM than in the FEM. These findings may have important clinical implications.